2019
DOI: 10.1093/qjmed/hcz261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of 3 days preoperative treatment with recombinant human erythropoietin in total knee arthroplasty surgery: a clinical trial

Abstract: Aims The purpose of study is to evaluate the effect and complication of preoperative short-term daily recombinant human erythropoietin (rhEPO) treatment for blood-saving in patients undergoing unilateral primary total knee arthroplasty (TKA). Methods This three-arm randomized clinical trial compared three different rhEPO-based treatment protocols for unilateral primary TKA. Group A: application of daily doses of rhEPO combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…A sample size analysis was performed to calculate the minimum number of patients necessary for this study. Based on our pilot study and previous literature 10 , the standard deviation of hemoglobin was assumed to be 15.0 g/L and a difference of >10.0 g/L in hemoglobin concentration was considered the minimal clinical difference. With the test of significant level as 0.05 and the power of test as 80%, the minimal sample size was calculated to be 35 per group (2‐tailed), which indicated that the number of patients enrolled in each group was sufficient for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample size analysis was performed to calculate the minimum number of patients necessary for this study. Based on our pilot study and previous literature 10 , the standard deviation of hemoglobin was assumed to be 15.0 g/L and a difference of >10.0 g/L in hemoglobin concentration was considered the minimal clinical difference. With the test of significant level as 0.05 and the power of test as 80%, the minimal sample size was calculated to be 35 per group (2‐tailed), which indicated that the number of patients enrolled in each group was sufficient for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous trials were performed to find out risk factors contributing to bleeding after procedure of TKA, and corresponding interventions were carried out to prevent further blood loss and avoid postoperative transfusion. For example, the erythropoietin taken before surgery could effectively stimulate erythropoiesis and improve preoperative and postoperative hemoglobin levels and decrease transfusion rate when combined with iron therapy, helping patients get over anemia 10 . According to our protocol, if the open‐box prosthesis is proved to cause more blood loss than the closed‐box prosthesis in patients undergoing unilateral or one‐stage bilateral TKA, the uncovered areas in the intercondylar fossa in the open‐box one should be regarded as a risk factor related with further postoperative bleeding, which benefits patients by informing surgeon's selection for knee prosthesis, such as not implanting open‐box prosthesis in patient with some other risk factors of bleeding or transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic transfusion carries a substantial risk of transfusion-associated complications requiring additional treatment and increased length of stay [ 4 ]. Many blood-saving strategies have been reported, of which recombinant human erythropoietin (rhEPO) has demonstrated effectiveness in reducing hemoglobin (Hb) level drop and blood transfusion requirements according to numerous randomized controlled trials [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One is weekly application of large-dose rhEPO for 2–4 weeks before surgery, which is called the long-term regimen [ 9 ]. The other one is daily application of small-dose rhEPO from 0–5 days preoperatively to a few days (less than a week) postoperatively, which is called the short-term regimen [ 5 , 6 , 7 , 8 ]. However, the weekly protocol has some obvious drawbacks: The long-term of treatment requested the patients to come back to hospital weekly for injections, which would therefore cause inconvenience to the patients and it would also increase the preoperative waiting interval.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation